Investment effects of capital gains taxation under simultaneous investment and abandonment flexibility - Rainer Niemann; Caren Sureth (Arbeitskreis Quantitative Steuerlehre (arqus), 2009)
The influence of capital gains taxes on investment decisions is a central issue of accounting and public finance research. However, the implications of capital gains taxes on investors' willingness to invest in irreversible projects with entry and exit flexibility have not yet been a focal issue. As a result, the effects of taxing capital gains on the interdependencies of investment and divestment decisions have to be identified, especially under timing flexibility. This paper closes this gap by simultaneously analyzing investment timing and abandonment decisions for risky irreversible investment projects with uncertain cash flows under differential tax rates for ordinary income and capital gains. We investigate whether capital gains taxes affect immediate and delayed investment asymmetrically. Furthermore, we investigate the impact of capital gains taxation on the optimal abandonment decision. Performing extensive numerical simulations we find that varying the liquidation proceeds affects the decision whether or not to postpone the investment decision. Higher cash flow volatility favors delayed investment. We find that the introduction of capital gains taxation tends to be harmful for immediate investment. Moreover, we show that taxing capital gains may induce a tax paradox for delayed investment. Depending on the pre-tax parameter setting the future value of delayed investment may even increase in absolute terms for increasing capital gains tax rates. For sufficiently high liquidation proceeds capital gains taxation tends to favor continuation of a project. We find taxing capital gains mainly induces other, but not necessarily less arbitrary distortions than exempting capital gains.
Keywords: 330